Iran awakening : one woman's journey to reclaim her life and country - ʻIbādī, Shīrīn (Random House Trade Pbk., 2007)
A NEW YORK TIMES NOTABLE BOOK - The moving, inspiring memoir of one of the great women of our times, Shirin Ebadi, winner of the 2003 Nobel Peace Prize and advocate for the oppressed, whose spirit has remained strong in the face of political persecution and despite the challenges she has faced raising a family while pursuing her work. Best known in this country as the lawyer working tirelessly on behalf of Canadian photojournalist, Zara Kazemi--raped, tortured and murdered in Iran--Dr. Ebadi offers us a vivid picture of the struggles of one woman against the system. The book movingly chronicles her childhood in a loving, untraditional family, her upbringing before the Revolution in 1979 that toppled the Shah, her marriage and her religious faith, as well as her life as a mother and lawyer battling an oppressive regime in the courts while bringing up her girls at home. Outspoken, controversial, Shirin Ebadi is one of the most fascinating women today. She rose quickly to become the first female judge in the country; but when the religious authorities declared women unfit to serve as judges she was demoted to clerk in the courtroom she had once presided over. She eventually fought her way back as a human rights lawyer, defending women and children in politically charged cases that most lawyers were afraid to represent. She has been arrested and been the target of assassination, but through it all has spoken out with quiet bravery on behalf of the victims of injustice and discrimination and become a powerful voice for change, almost universally embraced as a hero. Her memoir is a gripping story--a must-read for anyone interested in Zara Kazemi's case, in the life of a remarkable woman, or in understanding the political and religious upheaval in our world. Praise for Shirin Ebadi and Iran Awakening "This is the riveting story of an amazing and very brave woman living through some quite turbulent times. And she emerges with head unbowed."--Archbishop Desmond Tutu "The safety and freedom of citizens in democracies is irretrievably bound with the safety and freedom of people like Shirin Ebadi who are fighting to reassert the best achievements of mankind: universal human rights. One of the staunchest advocates for human rights in her country and beyond, Ms. Ebadi, herself a devout Muslim, represents hope for many in Muslim societies that Islam and democracy are indeed compatible."--Azar Nafisi "A moving portrait of a life lived in truth."--The New York Times Book Review "A riveting account of a brave, lonely struggle . . . [Iran Awakening] reads like a police thriller, its drama heightened by Ebadi's determination to keep up the quotidian aspects of her family life."--The Washington Post Book World "A must read . . . may be the most important book you could read this year."--Seattle Post-Intelligencer